Textile Industry In Yorubaland: Indigenous Knowledge And Modernity In The Era Of Globalisation. - Adu, Funmilayo Modupe; Ajayi, Adeyinka Thereza; Aremu, Johnson Olaosebikan (Advances in Social Sciences Research Journal, 2018)
Globalization it is accepted has made nonsense of state boarders. Issues that are local have become notable international concerns. Indigenous knowledge systems have not only been impacted by this phenomenon but have impacted other civilizations through the wildfire use of technology made available by globalization impacts. Modernity, by producing more refined and better accepted usable have brought indigenous knowledge of civilizations to the awareness of other civilizations ,cross weaving technologies to produce a new and modern conception that is better acceptable and more widely distributed. The traditional Yoruba aso oke is a product with such impact, having experienced a stage of modernization resulting from technological innovations made available from other nations through the benefits of globalization. Machines of various varieties such as tread making machines, industrial weaving machines, embroidery machines amongst others, have brought modernization to the Yoruba traditional weaving industry. This has not only created a smoother and better accepted version but also an increased distribution to provide a source of livelihood for a growing population of the citizens who engage in production and distribution in Nigeria and outside. This paper argues that the Yoruba weaving industry has been positively impacted by the globalization advantage to produce a more acceptable quality that has furthered the economic interest of the industry and internationalized the awareness of a growing traditional weaving textile industry that can further be exploited for national development.